Tissue oxidant, antioxidant and TNF-alpha levels in ureteropelvic junction obstructions Oxidative stress in ureteropelvic junction obstructions - Yagmur, Ilyas; Firdolas, Fatih; Pirincci, Necip (Bayrakol Medical Publisher, 2021)
Aim: In this study, it was aimed to determine the rote of some oxidant, antioxidant agents and tumor necrosis factor alpha (TNF-alpha) in the pathophysiology of ureteropelvic junction obstructions because of their effect on cell life, development and death. Material and Methods: A total of 56 patients who applied to the Urology Clinic of Firat University Hospital between 2015-2018 were included in the study. The patients were divided into two groups: 'patients' and 'controls'. In the 'patients' group, 30 patients with ureteropelvic junction obstruction were evaluated. In the 'control' group, 26 patients who were diagnosed with a kidney tumor or non-functional kidney were evaluated. TNF-alpha, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and malondialdehyde (MDA) levels were measured in the tissue samples taken from the uretero pelvic junction segments of the study groups. Results: MDA and TNF-alpha levels were detected to be significantly higher in the patient group than in the control group. SOD, CAT and GPx enzyme levels were lower in the patient group than in the control group (p <0,05). In the Pearson correlation graph, TNF-alpha revealed a negative correlation with SOD, CAT and GPx and a positive correlation with MDA. Also, a negative correlation was detected between SOD and MDA. Discussion: In our study, it was concluded that oxidative stress and antioxidant mechanisms may have a role in the pathophysiology of ureteropelvic junction obstructions. In this regard, antioxidants were thought to be useful in the prevention and treatment of ureteropelvic junction stenosis.
Keywords: Oxidant; Antioxidant; TNF-alpha; Ureteropelvic obstruction; MDA